PERILAKU KONSUMSI AIR MINUM PADA SISWA/SISWISMA NEGERI 3 MEDAN TAHUN 2015 - Yuni Dewi Hastuti; Ernawati Nasution; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
In order to improve public health status, it is need to be implemented various health attemps community including monitoring the quality of drinking water consumed by the public. Water is the main component in the body. Body can survive for weeks without food, but only days whithout water. The water is indispensable because it helps the formation of chemicals that the body needs. Every time human beings will lose water throughyour breath, perspiration, urine and bowel movements. So, that the body is fungtioning normally, then lose water must be replaced with sufficient drinking water.                This study is a descriptive survey observasional with cross sectional designof drinking water consumption of the students SMA Negeri 3 at Medan. The population in this study are all students of class X and XI at Medan that is 1142 person. The sample is a portion of the population that is 93 person. Data collection forms using form questionnaires. Processing and analysis of data is done by manual and computer with SPSS.            The results showed that the level of knowledge of the students is a good knowledge category, 58,1 %. The attitude of the average students in the category of either the 81,7 %. The type of beverage consumed an beverage student is a type of drink Tea whit the amount of 32,3 %. The level of water consumption average student enough to be seen there are as many as 46,2 % of students with the amount of consumption of less category.            The results showed that the school in order to control and provide intensive appeal to the school cook shop manager as a provider of food and beverage snacks for more attention to the food and drinks to be sold students.  Keywords : attitude, drinking water consumption, Senior high school